Self-objectification and sexual satisfaction: A preregistered test of the replicability and robustness of Calogero & Thompson (2009) in a sample of U.S. women. (December 2021) - Clapp, Abbie R.; Syed, Moin
Highlights: We conducted a U.S. replication and expansion of Calogero and Thompson (2009). Self-surveillance did not directly predict sexual satisfaction in any tested model. Sexual self-esteem and sexual satisfaction predicted one another across models. 3-5% of sexual satisfaction variance was accounted for by body image variables. All models showed good fit, though the hypothesized model's fit was best overall. Abstract: Objectification theory has provided a useful framework for the study of women's sexual outcomes. However, little research has been conducted on the role of self-objectification in predicting sexual satisfaction. We conducted a replication of Calogero and Thompson (2009a), which reported a direct relationship between self-surveillance and sexual satisfaction, and expanded upon their work. We tested four path analysis models: Calogero and Thompson's reported and hypothesized models, and two previously untested models, all containing our variables of interest (media internalization, self-surveillance, body shame, sexual self-esteem, and sexual satisfaction). Each model was tested with the full sample ( N = 349) and a restricted sample ( N = 127) that met Calogero and Thompson's relationship status and sexual frequency inclusion criteria, and with and without BMI covaried. Both samples consisted of U.S. college women recruited in Fall 2019, with a mean age of M = 19.68 in the restricted sample. Results showed good fit for all tested models but failed to replicate the direct pathway between self-surveillance and sexual satisfaction. Instead, our models supported an indirect effect of self-surveillance on sexual satisfaction through body shame and sexual self-esteem. Findings support the role of sociocultural channels in influencing college women's body image and sexual experiences.